Monetary and Fiscal Policy Design Issues in Low-Income Countries. (Policy Papers; Policy Paper, 2005)
Considers possible adjustments in the design of Fund-supported programs, drawing on the experience of low-income countries that have successfully addressed the most apparent domestic macroeconomic imbalances.